Adventure tourism, its environmental impact and mitigation proposal in the quebrada of Quillcayhuanca - Espinoza Muñoz, Einer (2017)
The purpose of this study was to investigate adventure tourism in the Quillcayhuanca Gorge, located in the Cordillera Blanca within the Huascarán National Park near the city of Huaraz, and determine how this activity with its different modalities impacts natural resources such as soil, water, air and depredating flora and fauna.It is presented in detail the processing and analysis of the data using as an instrument the survey to the residents of the community of Unchus and its annex Llupa who are the people who know the place and are involved with adventure tourism in Quillcayhuanca. We also performed the direct observation technique and to corroborate the data we used the documentary analysis. The results indicate that adventure tourism (53.7%) is the predominant activity with more than 1500 tourists who visit it annually. The environmental impact is directly related to the activity. The type of adventure tourism that generates the greatest impact is Trekking, with 46.3% and more than 70% of tourists are foreigners.Natural resources are seriously affected. The soil is quite affected (61% consider it so), water with 17.5% and air with 16.9%, because of adventure tourism. At present, programs for the prevention and conservation of the environment in the Quebrada of Quillcayhuanca are insufficient, tourism services are neglected and tourism is scarce.Based on this study, a mitigation proposal has been developed, in which the main impacts generated by adventure tourism are identified, as well as the corrective measures to be implemented by the competent agencies and thus provide a better service to the tourist.